Remaining Strength Estimation For AISI 1020 Carbon Steel Pipeline Internal Corrosion Using Finite Element Analysis - Sridaran Nair, Wamadevan Nair (IRC, 2021)
Pipelines in the petroleum industry suffer failure of any sort, as to any other equipment.